2016
DOI: 10.1111/fwb.12827
|View full text |Cite
|
Sign up to set email alerts
|

Do rivermouths alter nutrient and seston delivery to the nearshore?

Abstract: Summary Tributary inputs to lakes and seas are often measured at riverine gages, upstream of lentic influence. Between these riverine gages and the nearshore zones of large waterbodies lie rivermouths, which may retain, transform and contribute materials to the nearshore zone. However, the magnitude and timing of these rivermouth effects have rarely been measured. During the summer of 2011, 23 tributary systems of the Laurentian Great Lakes were sampled from river to nearshore for dissolved and particulate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 39 publications
3
31
0
Order By: Relevance
“…This is consistent with other studies that report phytoplankton transport from rivers to embayments (Larson et al, 2016). The riverine transport of phytoplankton into the bay was clearly important.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is consistent with other studies that report phytoplankton transport from rivers to embayments (Larson et al, 2016). The riverine transport of phytoplankton into the bay was clearly important.…”
Section: Discussionsupporting
confidence: 93%
“…Larson et al, 2016) , on the assumption that the model implies a continuous distribution between two finite and non-zero values if the percentage of river water never goes to zero. Larson et al, 2016) , on the assumption that the model implies a continuous distribution between two finite and non-zero values if the percentage of river water never goes to zero.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of the lower Grand have indicated that an appreciable portion of dissolved P is converted into phytoplankton biomass prior to entering Lake Erie (Kuntz, 2008). Despite the overall eutrophic conditions, the increasing disequilibrium from δ 18 O P_EQ at the river mouth during the summer in combination with high chlorophyll a concentrations (25-48 µg L −1 ) is not inconsistent with a highly productive river estuary where even the use of DOP can be important (Larson et al, 2016;Yuan et al, 2017). Further study of phosphorus sources to the lower river and speciation would be required to confirm such pathways, particularly in order to trace back to specific input sources of P. Nonetheless, even though riverine δ 18 O P appears to be altered prior to discharge into the lake, when our δ 18 O P data are considered together with evidence of strongly non-conservative mixing behavior of SRP, we infer that most of the P i discharged by the river is quickly assimilated into phytoplankton and rapidly overprinted via DOP recycling.…”
Section: Oxygen Isotope Ratios Cannot Be Used To Track Riverine Inputmentioning
confidence: 96%